Analysis of age, period, and birth cohort effects on suicide mortality in Brazil and the five major geographic regions - Pauliana Valéria Machado Galvão; Cosme Marcelo Furtado Passos da Silva (BMC, 2023)
Abstract Objective Estimate the effects of age, period, and birth cohort on suicide mortality in Brazil by major geographic region in the overall population and by sex. Methods This was a time trend ecological study. National and regional suicide mortality data from 1981 to 2020 were analyzed for the overall population and by sex. Age, period, and cohort effects were calculated with a Poisson regression model using estimable functions with the Epi package of the R statistical program, version 4.2.1. Results There were 272,716 suicides in individuals ranging from 20 to 79 years old. In the overall population, the age model-adjusted suicide mortality rates showed an upward pattern for Brazil. The most recent cohort showed the highest associated risk, 1.67 (95%CI 1.63; 1.71), while for the reference period, it was the highest risk among all the periods. Conclusions Suicide mortality rates have shown an upward trend with advancing age in both men and women in the Brazilian population. However, the behavior of the period effect and cohort depends on the population analyzed and regional distribution.